The map-based genome sequence of Spirodela polyrhiza aligned with its chromosomes, a reference for karyotype evolution - Cao, Hieu Xuan; Vu, Giang Thi Ha; Wang, Wenqin; Appenroth, Klaus J; Messing, Joachim; Schubert, Ingo (The New phytologist, 2016)
Duckweeds are aquatic monocotyledonous plants of potential economic interest with fast vegetative propagation, comprising 37 species with variable genome sizes (0.158-1.88 Gbp). The genomic sequence of Spirodela polyrhiza, the smallest and the most ancient duckweed genome, needs to be aligned to its chromosomes as a reference and prerequisite to study the genome and karyotype evolution of other duckweed species. We selected physically mapped bacterial artificial chromosomes (BACs) containing Spirodela DNA inserts with little or no repetitive elements as probes for multicolor fluorescence in situ hybridization (mcFISH), using an optimized BAC pooling strategy, to validate its physical map and correlate it with its chromosome complement. By consecutive mcFISH analyses, we assigned the originally assembled 32 pseudomolecules (supercontigs) of the genomic sequences to the 20 chromosomes of S. polyrhiza. A Spirodela cytogenetic map containing 96 BAC markers with an average distance of 0.89 Mbp was constructed. Using a cocktail of 41 BACs in three colors, all chromosome pairs could be individualized simultaneously. Seven ancestral blocks emerged from duplicated chromosome segments of 19 Spirodela chromosomes. The chromosomally integrated genome of S. polyrhiza and the established prerequisites for comparative chromosome painting enable future studies on the chromosome homoeology and karyotype evolution of duckweed species.
Keywords: duckweeds; genome integration; Chromosomes, Artificial, Bacterial; fyzikální mapování chromozomů; umělé bakteriální chromozomy; Genome, Plant; genom rostlinný; karyotypizace; hybridizace in situ fluorescenční; molecular cytogenetic map; Karyotyping; molekulární evoluce; karyotyp; Evolution, Molecular; Spirodela polyrhiza; Genomics; chromozomy rostlin; Chromosomes, Plant; Physical Chromosome Mapping; fluorescence in situ hybridization (FISH); In Situ Hybridization, Fluorescence; Karyotype; Araceae; genomika